Resíduos de poluentes orgânicos persistentes em mel de abelhas: repercussões da contaminação ambiental - Mohr, Susana (2013)
Persistent Organic Pollutants (POPs) are chemical substances that are widely distributed throughout the environment, accumulate in the fatty tissue of living organisms, are found at higher concentrations in the food chain and are toxic to both humans and wildlife. In the present work, POPs were determined in honey samples from different geographic regions, evaluating both the quality and safety of honey as food, and the environmental contamination of the studied regions. Organochlorine pesticides were analysed in 186 samples from the South region of Brazil, with concentrations between <LOQ and 92 ng g-1. Pesticides Endosulfan alpha and Endosulfan sulfate were the most frequent, with mean of 1.84 and 1.68 ng g-1, respectively. Samples from Santa Catarina State had higher Aldrin concentrations when compared to those from Rio Grande do Sul and Paraná States, while there was a reduction in the Endrin concentration in the samples collected in 2011, when compared with those collected in 2010. With regard to food security, 18% of the samples exceeded the maximum residue limits allowed by law for compounds Aldrin, p,p'-DDT, Endosulfan alpha, Endrin, and Heptachlor, which may pose a risk to consumer health. Indicator PCBs were analysed in 137 samples from Rio Grande do Sul, Santa Catarina, Paraná, and São Paulo States. PCBs 28 and 52 were the most frequent, with means of 1.18 and 0.74 ng g-1, respectively. Samples from São Paulo State exhibited the highest levels (ΣPCBs 7.52 ng g-1), followed by samples from Paraná (ΣPCBs 5.4 ng g-1), Santa Catarina (ΣPCBs 2.59 ng g-1), and Rio Grande do Sul (ΣPCBs 1.24 ng g-1), with significant difference for PCBs 28 and 52. There was no difference between the concentrations of samples collected in the years 2009, 2010, and 2011. DL-PCBs, PCDDs and PCDFs were analysed in 16 samples from four Brazilian States (RS, SC, PR and SP). DL-PCB concentrations ranged between 24.3 and 260 pg g-1, while PCDD/Fs, between <LOD and 5.4 pg g-1. TEQ values were between 0.002 and 0.343 pg WHO-TEQ g-1. No significant difference was found among the concentration levels of the samples from the four States. Brominated flame retardants (PBDEs, BTBPE and DBDPE) were analysed in 35 honey samples from Brazil, Spain, Portugal, Morocco, and Slovenia, with concentrations ranged between <LOD and 24.7 pg g-1. Brazilian honeys exhibited the highest mean concentration (5.19 pg g-1), followed by Moroccan (4.4 pg g-1), Portuguese (2.24 pg g-1), Spanish (1.77 pg g-1), and Slovenian (0.93 pg g-1) samples. PBDE 47 was the most frequent, being detected in 91% of samples, and followed by PBDE 99, in 63%. These compounds were the main contributors in the BFR total concentration in samples from Europe, while the novel flame retardants, BTBPE and DBDPE, had greater contribution in samples from Brazil and Morocco. With regard to food security, there is no limit established by law for PCBs, PCDDs, PCDFs, and BFRs in honey. Although the levels detected were quite low when compared to other foods of animal origin, the honey samples analysed showed significant contamination, demonstrating that the studied regions contain sources of environmental contamination to be investigated.